Exergetic sustainability analysis of municipal solid waste treatment systems: A systematic critical review. (March 2022) - Soltanian, Salman; Kalogirou, Soteris A.; Ranjbari, Meisam; Amiri, Hamid; Mahian, Omid; Khoshnevisan, Benyamin; Jafary, Tahereh; Nizami, Abdul-Sattar; Gupta, Vijai Kumar; Aghaei, Siavash; Peng, Wanxi; Tabatabaei, Meisam; et al.
Abstract: The growing volume of municipal solid waste (MSW) generated worldwide often undergoes open dumping, landfilling, or uncontrolled burning, releasing massive pollutants and pathogens into the soil, water, and air. On the other hand, MSW can be used as a valuable feedstock in biological and thermochemical conversion processes to produce bioenergy carriers, biofuels, and biochemicals in line with the United Nations' Sustainable Development Goals (SDGs). Valorizing MSW using advanced technologies is highly energy-intensive and chemical-consuming. Therefore, robust and holistic sustainability assessment tools should be considered in the design, construction, and operation phases of MSW treatment technologies. Exergy-based methods are promising tools for achieving SDGs due to their capability to locate, quantify, and comprehend the thermodynamic inefficiencies, cost losses, and environmental impacts of waste treatment systems. Therefore, the present review paper aims to comprehensively summarize and critically discuss the use of exergetic indicators for the sustainability assessment of MSW treatment systems. Generally, consolidating thermochemical processes (mainly incineration and gasification) with material recycling methods (plastic waste recovery), heat and power plants (steam turbine cycle and organic Rankine cycle), modern power technologies (fuel cells), and carbon capture and sequestration processes could improve the exergetic performance of MSW treatment systems. Typically, the overall exergy efficiency values of integrated MSW treatment systems based on the incineration and gasification processes were found to be in the ranges of 17–40% and 22–56%, respectively. The syngas production through the plasma gasification process could be a highly favorable waste disposal technique due to its low residues and rapid conversion rate; however, it suffers from relatively low exergy efficiency resulting from its high torch power consumption. The overall exergy efficiency values of integrated anaerobic digestion-based MSW processing systems (34–73%) were generally higher than those based on the thermochemical processes. Exergy destruction and exergy efficiency were the most popular exergetic indicators used for decision-making in most published works. However, exergoeconomic and exergoenvironmental indices have rarely been used in the published literature to make decisions on the sustainability of waste treatment pathways. Future studies need to focus on developing and realizing integrated waste biorefinery systems using advanced exergy, exergoeconomic, and exergoenvironmental methods. Highlights: Exergetic aspects of municipal solid waste treatment processes are critically reviewed. Merits and demerits of exergetic indices to study waste treatment systems are highlighted. Combining thermochemical processes with heat/material recovery could be a sustainable strategy. Advanced power generation technologies can improve waste treatment systems exergetically. Integrated waste management systems should be developed using advanced exergy-based methods.